Komunikasi Matematis Dalam Terang Literasi Matematika - Kristianus Viktor Pantaleon; Fransiskus Nendi; Emilianus Jehadus (UNIKA SANTU PAULUS RUTENG, 2019)
This descriptive theoretical study aims to explain in detail and complete aspects of mathematical communication in mathematical literacy. Communication in mathematical literacy has two important components, namely receptive and constructive. In each process of solving a problem, the two components of communication will always be contained. Professional teachers must properly understand the two components in order to measure students' mathematical communication skills correctly. To be easy to understand, the two components must be conveyed or stated correctly, coherently, and clearly. Emphasis on these three components then distinguishes mathematical communication from other mathematical abilities, such as problem solving, reasoning and proof, connection and representation